2020
DOI: 10.1039/d0sc04508j
|View full text |Cite
|
Sign up to set email alerts
|

Single-emissive-layer all-perovskite white light-emitting diodes employing segregated mixed halide perovskite crystals

Abstract: Metal halide perovskites have demonstrated impressive properties for achieving efficient monochromatic light-emitting diodes. However, the development of white perovskite light-emitting diodes (PeLEDs) remains a big challenge. Here, we demonstrate a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Adapted from paper reference. [185] Our findings reveal that single-EML all-perovskite white LEDs are possible via effective modulation of perovskite precursor solution, which will spur new development of high-performance white PeLEDs.…”
Section: Single-eml All-perovskite White Ledsmentioning
confidence: 74%
See 1 more Smart Citation
“…Adapted from paper reference. [185] Our findings reveal that single-EML all-perovskite white LEDs are possible via effective modulation of perovskite precursor solution, which will spur new development of high-performance white PeLEDs.…”
Section: Single-eml All-perovskite White Ledsmentioning
confidence: 74%
“…Adapted from paper reference. [185] The effective modulation of the perovskite precursor solution is the key to the suppression of anion exchange and energy transfer. The secondary electron (SE) image in Figure 5.6a shows that there are two different types of grains in the perovskite film, rod-like (like Point 1) and plate-like grains (like Point 2).…”
Section: Single-eml All-perovskite White Ledsmentioning
confidence: 99%
“…Many PeLEDs have been demonstrated with EQEs higher than 20% in the green 75 77 , red 78 , 79 , and near-infrared 80 82 regions. In addition to these exciting results, WPeLEDs, especially SEL–WPeLEDs, have also been developed rapidly 26 29 , 83 87 . In 2016, just after some of the earliest reports of PeLEDs, a SEL-WPeLED (Fig.…”
Section: Cases Of Wleds With a Single Emissive Layermentioning
confidence: 99%
“…In addition, perovskite as an SEL with different components has also been proven to achieve white electroluminescence, and the device structure is shown in Fig. 8e 87 . In this device, an organic material (benzamidine hydrochloride, BHCl) successfully controlled the perovskite precursor solution to form segregated CsPb(Br 1− x Cl x ) 3 and CsPb(Br 1− y I y ) 3 grains (Fig.…”
Section: Cases Of Wleds With a Single Emissive Layermentioning
confidence: 99%
“…Gao et al reported a single-emissive layer all-perovskite white PLED, in which the perovskite film consists of separated mixed halide perovskite phases with blue and red emission. 29 The authors believed that benzamidine hydrochloride (BHCl) and PbBr 2 are the key factors leading to the segregation of phases with blue and red emission. 29 In our research, we found that even without large organic ligands, Cs large organic ligands might not be the decisive factor that leads to dual emission.…”
mentioning
confidence: 99%